Treating a rare mid-term complication of transapical transcatheter aortic valve implantation (TAVI): a case report. Issue 1 (31st December 2022) - Fraccalanza, Eugenio; Fin, Alessandra; Zingaretti, Nicola; Contessi Negrini, Filippo; Mazzaro, Enzo; Livi, Ugolino; Parodi, Pier Camillo
Abstract: We report the case of a patient who underwent transcatheter aortic valve implantation via left anterior mini-thoracotomy in whom a periapical subcutaneous collection appeared in the anterior thoracic wall 18 months after the procedure. The tissue defect was efficaciously repaired via intercostal artery perforator flap, preserving the thoracodorsal and internal mammary arteries.